2018
DOI: 10.3390/f9060312
|View full text |Cite
|
Sign up to set email alerts
|

Improved Estimates of Biomass Expansion Factors for Russian Forests

Abstract: Biomass structure is an important feature of terrestrial vegetation. The parameters of forest biomass structure are important for forest monitoring, biomass modelling and the optimal utilization and management of forests. In this paper, we used the most comprehensive database of sample plots available to build a set of multi-dimensional regression models that describe the proportion of different live biomass fractions (i.e., the stem, branches, foliage, roots) of forest stands as a function of average stand ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 16 publications
4
51
1
5
Order By: Relevance
“…This wide range of uncertainty highlights the need for providing locally-fit models. This tendency was also reflected in the study of Schepaschenko et al [41], who found high-level geographic variability of BCEFs values across climatic gradients in Russia. The high variability of BCEFs provided by IPCC is most probably connected with its wide range of geographic origin: among eight source studies one comes from China, one form Japan, one from Australia, four from USA and one from Germany.…”
Section: Accuracy Of Stand-level Biomass Modelssupporting
confidence: 61%
See 4 more Smart Citations
“…This wide range of uncertainty highlights the need for providing locally-fit models. This tendency was also reflected in the study of Schepaschenko et al [41], who found high-level geographic variability of BCEFs values across climatic gradients in Russia. The high variability of BCEFs provided by IPCC is most probably connected with its wide range of geographic origin: among eight source studies one comes from China, one form Japan, one from Australia, four from USA and one from Germany.…”
Section: Accuracy Of Stand-level Biomass Modelssupporting
confidence: 61%
“…Analysis of accuracy of our and published models for biomass estimation at the stand level revealed that height-based models and estimation using BCEF models provided the lowest biases ( Figure 6, NSE of 0.81 and 0.99, respectively). Approaches recommended by IPCC and Schepaschenko et al [41] provided overestimated biomass, which deviated the most in cases of the biggest forest stands (NSE of −0.86, −0.23 and 0.40, respectively). Models provided by Teobaldelli et al [24] provided lower overestimation of L. decidua biomass (NSE of 0.77 and 0.99, for age-and volume-based models, respectively).…”
Section: Comparison Of Stand Level Biomass Modelsmentioning
confidence: 92%
See 3 more Smart Citations